2019
DOI: 10.1017/s0033291719003222
|View full text |Cite
|
Sign up to set email alerts
|

Social reinforcement learning as a predictor of real-life experiences in individuals with high and low depressive symptomatology

Abstract: Background Several studies have reported diminished learning from non-social outcomes in depressed individuals. However, it is not clear how depression impacts learning from social feedback. Notably, mood disorders are commonly associated with deficits in social functioning, which raises the possibility that potential impairments in social learning may negatively affect real-life social experiences in depressed subjects. Methods Ninety-two participants with high (HD; N = 40) and low (LD;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 56 publications
4
26
0
Order By: Relevance
“…This idea is supported by the supplementary analysis of the present study which shows that the interaction between enhanced task uncertainty and inhibitory uncertainty intolerance predicts reduced social engagement motivation. In addition, the above suggestion is in line with our previous findings showing that increased negative social feedback expectancies are associated with social disengagement in individuals with high depressive symptomatology (Frey et al, 2019).…”
Section: Uncertainty About Social Outcomes Predicts Reduced Social Ensupporting
confidence: 92%
See 1 more Smart Citation
“…This idea is supported by the supplementary analysis of the present study which shows that the interaction between enhanced task uncertainty and inhibitory uncertainty intolerance predicts reduced social engagement motivation. In addition, the above suggestion is in line with our previous findings showing that increased negative social feedback expectancies are associated with social disengagement in individuals with high depressive symptomatology (Frey et al, 2019).…”
Section: Uncertainty About Social Outcomes Predicts Reduced Social Ensupporting
confidence: 92%
“…Deficits in social functioning are commonly observed in major depressive disorder (MDD; Katz, Conway, Hammen, Brennan, & Najman, 2011;Rhebergen et al, 2010;Rottenberg & Gotlib, 2008). Compared to controls, depressed individuals have fewer friends (Brim et al, 1982;Frey et al, 2019;Youngren and Lewinsohn, 1980), fewer intimate relationships (Gotlib and Lee, 1989), and spend less time with people in their social circle (Youngren and Lewinsohn, 1980). Additionally, depressed subjects show inappropriate behaviour during social interactions (reviewed in Rottenberg & Gotlib, 2008;Segrin, 2000), which can result in the receipt of negative feedback from other people (Segrin and Abramson, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Sweeney in their study showed that normative beliefs are predictors of persistence of physical activity (Sweeney, Wilson, & Van Horn, 2017). Thus, studies have shown that positive social life is a good predictor of PA (Frey, Frank, & McCabe, 2019).…”
Section: Discussionmentioning
confidence: 95%
“…Sweeney in their study showed that normative beliefs are predictors of persistence of physical activity (Sweeney, Wilson, & Van Horn, 2017). Thus, studies have shown that positive social life is a good predictor of PA (Frey, Frank, & McCabe, 2019).…”
Section: Discussionmentioning
confidence: 99%